Estimating the accuracy of muscle response testing: two randomised-order blinded studies. Issue 1 (December 2016) - Jensen, Anne; Stevens, Richard; Burls, Amanda
Abstract Background Manual muscle testing (MMT) is a non-invasive assessment tool used by a variety of health care providers to evaluate neuromusculoskeletal integrity, and muscular strength in particular. In one form of MMT called muscle response testing (MRT), muscles are said to be tested, not to evaluate muscular strength, but neural control. One established, but insufficiently validated, application of MRT is to assess a patient's response to semantic stimuli (e.g. spoken lies) during a therapy session. Our primary aim was to estimate the accuracy of MRT to distinguish false from true spoken statements, in randomised and blinded experiments. A secondary aim was to compare MRT accuracy to the accuracy when practitioners used only their intuition to differentiate false from true spoken statements. Methods Two prospective studies of diagnostic test accuracy using MRT to detect lies are presented. A true positive MRT test was one that resulted in a subjective weakening of the muscle following a lie, and a true negative was one that did not result in a subjective weakening of the muscle following a truth. Experiment 2 replicated Experiment 1 using a simplified methodology. In Experiment 1, 48 practitioners were paired with 48 MRT-naïve test patients, forming unique practitioner-test patient pairs. Practitioners were enrolled with any amount of MRT experience. In Experiment 2, 20 unique pairs were enrolled, with test patients being a mix of MRT-naïve and not-MRT-naïve. The primary index test was MRT. A secondary index test was also enacted in which the practitioners made intuitive guesses ("intuition"), without using MRT. The actual verity of the spoken statement was compared to the outcome of both index tests (MRT and Intuition) and their mean overall fractions correct were calculated and reported as mean accuracies. Results In Experiment 1, MRT accuracy, 0.659 (95% CI 0.623 - 0.695), was found to be significantly different (p < 0.01) from intuition accuracy, 0.474 (95% CI 0.449 - 0.500), and also from the likelihood of chance (0.500; p < 0.01). Experiment 2 replicated the findings of Experiment 1. Testing for various factors that may have influenced MRT accuracy failed to detect any correlations. Conclusions MRT has repeatedly demonstrated significant accuracy for distinguishing lies from truths, compared to both intuition and chance. The primary limitation of this study is its lack of generalisability to other applications of MRT and to MMT. Study registration The Australian New Zealand Clinical Trials Registry (ANZCTR;www.anzctr.org.au ; ID #ACTRN12609000455268, and US-based ClinicalTrials.gov (ID #NCT01066312 ). Abstrakt Ziele Abschätzung der Treffgenauigkeit von kinesiologischem, manuellem Muskelabtasten (Muskelabtasten im kinesiologischen Stil) (MRT) zum Unterscheiden zwischen Lügen und Wahrheit in gesprochenen Aussagen. Studiendesign Zwei prospektive Studien über diagnostische Treffgenauigkeit von MRT zur Entdeckung von Lügen werden präsentiert. Eine tatsächlich positives MRT Testresultat liegt vor, wenn eine Muskelabschwächung resultierte und ein tatsächlich negatives MRT bei keiner Muskelabschwächung. Versuch 2 wiederholte Versuch 1 unter Anwendung einer vereinfachten Methodik. Durchführungsort Private Praxen in Grossbritannien und Vereinigte Staaten, mit einem Fundus an Testpatienten (TPs) aus der lokalen Gesellschaft. Teilnehmende Im Versuch 1, 48 Fachausübende wurden mit 48 MRT unbefangenen TPs verkuppelt und formten damit einmalige Paare von Fachausübenden-TP („Paare"). Fachausübende mit irgend welcher MRT Erfahrung wurden zugelassen. Im Versuch 2 wurden 20 einmalige Paare zugelassen, wobei die TPs aus einem Mix von MRT Unbefangenen und Befangenen bestanden. Testindex Der prmäre Testindex war MRT. Ein sekundärer Testindex wurde ebenfalls durchgeführt, bei welchem die Fachausübenden intuitive Vermutungen („Intuition"), ohne Anwendung von MRT., anstellten. Angewendeter Standardtest (Referenzstandardtest) Der effektive Wahrheitsgehalt der gesprochenen Aussage wurde verglichen mit dem Resultat des Textindex und das Gesamtmittel des korrekten. Aussageanteils wurde berechnet und als durchschnittliche Treffgenauigkeit ausgewiesen. Resultate Im Versuch 1, MRT Treffgenauigkeit, 0.659 (95% CI 0.623 - 0.695), wurde als signifikant unterschiedlich (p < 0.01) von intuitiver Treffgenauigkeit, 0.474 (95% CI 0.449 - 0.500), und wie auch von der Zufallswahrscheinlichkeit (0.500; p < 0.01) identifiziert. Experiment 2 reproduzierte die Ergebnisse des Versuchs 1. Es konnten keine Korrelationen von anderen Faktoren identifiziert werden, welche die MRT Treffgenauigkeit hätten beeinflussen können. Fazit MRT hat wiederholt signifikante Treffgenauigkeit zum Unterscheiden zwischen Lügen und Wahrheit gezeigt im Vergleich zu Intuition und Zufall. Die primäre Einschränkung dieser Studie liegt in Mangel der Uebertragbarkeit auf andere Anwendungsgebiete der MRT.